Predstoyashchii match - kompyuternaya versiya - Polozov, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The article is devoted to the modelling a possible variant of forthcoming match. This is reached by the receiving the follows: 1. Universal pedagogical actions of rivals estimation by their participation in dynamics attacks, receiving on that base by means of the system of linear equations of estimation the players. Estimation allows to get the result of the resisting any pairs of rivals - participants of match. 2. Games's algorhythm. Tactics of the game they understand as the ways of redistribution the play load in the benefit the stronger partners on the postions of weakerivals. The efficacy of participant's game is characterized by the degree of realisation such direction of the game. That allows to control the changes during the game, and becomes the determing factor in the possibility of creation a computer version. 3. The player receives a possibility to develop the technic-tactical mentality. He can observe of the possible development of events and by means of the "mouse" to interfere the game gradually making it more effective. The model carries the universal character for playing kinds of sport.